Elucidating the interactions between carbon nanotubes and carbon black with styrene butadiene rubber. Issue 46 (9th July 2021) - García, Daniela B.; Mansilla, Marcela A.; Monsalve, Leandro N.; Bilbao, Emanuel; Garraza, Ana Lucía Rodríguez; Escobar, Mariano M.
Abstract: The reinforcement mechanism of carbon nanotubes (CNT) on styrene butadiene rubber is studied through dynamic and swelling tests. Compounds containing carbon black (CB) and an unfilled one were prepared for comparison purposes. The dynamic properties are interpreted through the Maier‐Göritz model to distinguish the contributions of stable and unstable crosslinks to the storage modulus, finding that the unstable ones become more relevant in samples containing a CNT concentration higher than 5 phr. In addition, the crosslinks density estimated by swelling and the stable contribution obtained with dynamical properties present the same tendency with the CNT amount. The former presents lower values, which can be explained considering that only stable crosslinks remain in the equilibrium‐swollen state, while in the second one both stable and unstable are considered. In addition, differences in the filler‐polymer interaction mechanisms are observed according to the morphology and aspect ratio of CNT in contrast to CB. Abstract : Graphical Abstract